3‐D numerical simulations on flow and mixing behaviors in gas–liquid–solid microchannels. Issue 6 (7th March 2013) - Can, Tang; Mingyan, Liu; Yonggui, Xu
<x xml:space="preserve">Abstract</x> Three‐dimensional (3‐D) gas‐liquid–solid flow and mixing behaviors in microchannels were simulated by coupled volume of fluid and discrete phase method and simulations were validated against observations. The detachment time and length of gas slug are shortened in liquid–solid flow, compared with those in liquid flow due to higher superficial viscosity of liquid–solid mixture, which will move the bubble formation toward the dripping regime. Solid particles mainly distribute in liquid slug and particle flow shows obvious periodicity. With the increase of contact angle of the inner wall, gas slug (0–50°), stratified (77–120°), and liquid drop (160°) flows are observed. The residence time distributions of solid and liquid phases are similar because particles behave as tracers. The backmixing of solid and liquid phases in liquid drop flow is the weakest among the three flow patterns, and the backmixing of gas phase in slug flow is weaker than that in both stratified and liquid drop flows. The results can provide a theoretical basis for the design of microreactors. © 2013 American Institute of Chemical Engineers AIChE J, 59: 1934–1951, 2013